2015
DOI: 10.5897/jde2015.0084
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of central obesity in rural South-Western Nigeria: Need for targeted prevention

Abstract: Obesity has reached epidemic proportions globally, and is now prevalent in low-income and middleincome countries. This study sets out to determine the prevalence of obesity as well as its predictors in rural South-Western Nigeria. Cross-sectional descriptive survey of 416 participants aged 20 to 70 years in two rural communities in Remo North Local Government area of Ogun State, Nigeria was taken. Relevant clinical and demographic parameters were obtained. Participants were screened for generalized and central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
5
1
1
Order By: Relevance
“…The prevalence of central obesity in this study was in line with the finding from the studies conducted in Wolaita Sodo 52.7%, 42 Gondar 58.5%, 43 and southwestern Nigeria 56.8%. 44 However, our finding was higher than the studies conducted in Dodoma region of Tanzania 24.88%, 20 Jimma University Teaching hospital 26%, 24 and the study in Addis Ababa 49.4%. 30 This might be due to the fact that there is a considerable difference in the study periods, place, and operational definition they use for central obesity.…”
Section: Discussioncontrasting
confidence: 74%
“…The prevalence of central obesity in this study was in line with the finding from the studies conducted in Wolaita Sodo 52.7%, 42 Gondar 58.5%, 43 and southwestern Nigeria 56.8%. 44 However, our finding was higher than the studies conducted in Dodoma region of Tanzania 24.88%, 20 Jimma University Teaching hospital 26%, 24 and the study in Addis Ababa 49.4%. 30 This might be due to the fact that there is a considerable difference in the study periods, place, and operational definition they use for central obesity.…”
Section: Discussioncontrasting
confidence: 74%
“…EC ranged between 885µs/cm to 910 µs/cm. TDS indicates the general nature of water quality or salinity 15 . During the study TDS is found between ranged 887 mg/l to 907 mg/l.…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…Sulphate is a non toxic anion but ailment like catharsis, dehydration and gastrointestinal irritation have been linked with it when concentration is high [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…Raimi juga menjelaskan bahwa responden yang mengalami obesitas sentral berada di wilayah rural. 8 Penelitian lain menemukan bahwa obesitas sentral mengalami kenaikan yang cepat di daerah rural dibandingkan dengan obesitas menurut Indeks Massa Tubuh. Angka obesitas sentral terbesar pada penduduk usia 18-65 tahun di China terjadi pada tahun 2011 dengan persentase di daerah urban 29,6% dan di daerah rural sebesar 30,6%.…”
Section: Pendahuluanunclassified